2022
DOI: 10.3390/jintelligence10040110
|View full text |Cite
|
Sign up to set email alerts
|

Where Does Eureka Come From? The Effect of Unreportable Hints on the Phenomenology of Insight

Abstract: Insight interests researchers given its special cognitive mechanisms and phenomenology (an Aha! experience or Eureka moment). There is a considerable amount of research on the effect of hints on performance in insight problem solving. However, only a few studies address the effect of hints on the subjective experiences of solvers, and the picture their results provide is unclear. We analyze the effect of unreportable true and false hints on different dimensions of the Aha! experience (subjective suddenness, Ah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…experience to different extents. For example, Ammalainen and Moroshkina (2022) demonstrated that unreportable semantic hints (which presumably increased processing fluency) affected the participants' subjective suddenness of comprehending the solutions, but not their confidence ratings.…”
Section: Discussionmentioning
confidence: 99%
“…experience to different extents. For example, Ammalainen and Moroshkina (2022) demonstrated that unreportable semantic hints (which presumably increased processing fluency) affected the participants' subjective suddenness of comprehending the solutions, but not their confidence ratings.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to measure the effect of training by means of self-ratings of creativity (Bergum and Bergum 1979). The recent literature on insight problem solving and creativity has begun to pay more attention to the phenomenal or meta-cognitive experience of the reasoner engaged in the task (e.g., Moroshkina 2021, 2022;Danek et al 2014Danek and Wiley 2017;Kaufman et al 2016;Laukkonen and Tangen 2018;Moroshkina et al 2022;Pétervári and Danek 2019;Shen et al 2016;Spiridonov et al 2021). It would thus be worth exploring whether being prompted to think in opposites is perceived by the reasoners themselves as useful and stimulating, as well as indicating how this impacts their motivation.…”
Section: Methodological and Theoretical Questions For A Future Resear...mentioning
confidence: 99%
“…In other words, the lack of conscious access to the unfolding cognitive processes is the reason for subjectively sudden solutions. For example, several demonstrated that unconscious cues can trigger insightful solutions ( Bowden, 1997 ; Ammalainen and Moroshkina, 2022 ).…”
Section: Introductionmentioning
confidence: 99%